Computing gold cluster energies with density functional theory: the importance of correlation. Issue 27 (2nd July 2021) - Ferrari, Piero; Hansen, Klavs
Abstract : Calculating energy-dependent properties on gold clusters via density functional theory depend critically on the choice of functional. Here we use measured dissociation energies as benchmark data for testing the performance of different functionals. Abstract : Energies calculated with density functional theory depend critically on the choice of the exchange–correlation functional. In this work, we use measured dissociation energies of Au n + ( n = 5–17) clusters as benchmark data to test two very different functionals for calculating total energies in these clusters; the simpler (and fast) PBE and the evolved (and expensive) B2PLYP double-hybrid functionals. PBE consistently gives poor agreement with the experimental results. In contrast, the B2PLYP functional, which implicitly includes electron correlation by performing a perturbative second-order correction, significantly improves the agreement of the calculations, at the cost of much more demanding computations. The better performance of the double-hybrid functional is ascribed to the longer range of the interatomic potential.